Leucocyte migration inhibition in liver disease - Vergani, C. (1974)
Clinical and histological features provide evidence that immunological reactions of the cell-mediated type are abnormal in some forms of chronic liver disease. By using the leucocyte migration test of Søborg and Bendixen (1967), a correlate of cellular hypersensitivity in vitro, the authors studied the production of the migration inhibitory factor by lymphocytes exposed to a fetal liver homogenate in 88 patients with acute and chronic liver disease. Abnormality of leucocyte migration was found in aggressive chronic hepatitis (inhibition in 67% of patients), cryptogenic cirrhosis (inhibition in 43%, stimulation in 13% of patients), and primary biliary cirrhosis (stimulation in two, inhibition in two out of six patients). The results are compatible with the hypothesis that cellular immune response to liver antigens is important in the pathogenesis of such diseases.